Evaluation of immune status among regular Malay male whole blood donors - Fauzi, Norhayati (2017)
Blood donations are an essential part of healthcare system. It is crucial to ensure that sufficient and safe supplies of blood from blood donation. However, it is important to ensure that the donor‟s health is not compromised by the donation of blood or blood component. Whole blood donors may lose approximately 2x109 leukocytes in a single whole blood donation, with no significant drop in peripheral blood lymphocyte count. The possibility of blood donation may change the immune status should be assessed. This study aimed to evaluate and compare the levels of immune markers among first time and regular whole blood donors, as well as, to determine association between the levels of immune markers with the frequency of whole blood donation. A comparative cross sectional study was done at Hospital USM from May 2015 to April 2016. Peripheral blood was taken from 40 regular and 40 first time; Malay male whole blood donors. The immune marker parameters that were studied included TWBCs with neutrophils, lymphocytes, monocytes, eosinophils and basophils count by using XE 5000 Sysmex haematology analyzer (Koba, Japan). Flow cytometry for percentage and absolute count of CD3, CD4, CD8, CD16+56+, CD19 and CD4:CD8 ratio using BD FACSCANTO II. IL-2, IL-10 and IFNγ level quantification by using ELISA immunoassay. IgG, IgA and IgM level quantification by using nephlometry. The mean (SD) of monocytes absolute count in first time and regular whole blood donors were 0.51 (0.14) and 0.58 (0.16), respectively with p value significantly higher in regular whole blood donors. The mean (SD) of interleukin 10 in first time and regular whole blood donors were 6.60 (3.05) and 5.04 (2.28), respectively with p value significantly lower in regular whole blood donors. The mean (SD) of Ig A in first time and regular whole blood donors were 2.24 (0.89) and 2.71(1.02), respectively with mean value significantly higher in regular whole blood donors. Other parameters showed no significant mean different. Analysis for determination of association between the levels of immune markers with frequency of whole blood donation showed no significant association. This present study demonstrates regular blood donors showed no serious significant effects both for cellular and humoral immune markers when compared with the first time blood donors. The differences in monocytes absolute count, IL-10 and IgA between the two groups are probably related to variation of immune activity with no clinical significance. Furthermore, there was no significant association between the levels of immune markers with frequency of whole blood donation. Within limitations of this present study, there are no added risks to regular blood donors as a result of immune changes.